2022
DOI: 10.14349/rlp.2022.v54.21
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación y validación transcultural al español del University Student Engagement Inventory

Abstract: Introducción: el compromiso académico hace referencia a la predisposición que los estudiantes tienen a participar de manera activa en la vida universitaria, asistiendo a las clases, entregando los trabajos a tiempo y siguiendo las instrucciones de los docentes. Existe evidencia que demuestra que el compromiso académico predice positivamente el éxito de los estudiantes. Por esta razón, es que su evaluación cobra gran relevancia para el ámbito educativo universitario a la hora de diseñar prácticas pedagógicas qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Comparing the results of our study with those of Albornoz et al [51], who specifically focused on Engineering students in Chile using the USEI, the results from their study showed that the USEI had good psychometric properties and a three-factor solution. Similarly, in the study by Freiberg-Hoffmann et al [52], the USEI was adapted and validated in Spanish for use in Latin American countries. Their results showed that the adapted USEI had good psychometric properties, with a three-factor solution similar to the results in this study [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the results of our study with those of Albornoz et al [51], who specifically focused on Engineering students in Chile using the USEI, the results from their study showed that the USEI had good psychometric properties and a three-factor solution. Similarly, in the study by Freiberg-Hoffmann et al [52], the USEI was adapted and validated in Spanish for use in Latin American countries. Their results showed that the adapted USEI had good psychometric properties, with a three-factor solution similar to the results in this study [52].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the three factors of the constructed model showed good reliability. For example, a study was carried out with Chilean Engineering students [51], and another crosscultural validation was performed in Spanish, with Spanish, Argentinian, and Uruguayan students [52]. Moreover, a version of the USEI was validated with Turkish university students [53].…”
Section: Introductionmentioning
confidence: 99%
“…La evidencia de validez externa fue testeada, arrojando resultados favorables en las correlaciones de Pearson con la escala de autoestima de Rosenberg (rses). El patrón de correlaciones observadas entre el FoMO y la autoestima, evaluada a través de la rses en este estudio, arrojó como resultado una correlación baja pero significativa, lo cual es consistente con lo reportado en estudios previos (Buglass, et al, 2017;Torres-Serrano, 2020;Freiberg-Hoffmann et al, 2022). De esta forma, nos proporciona evidencia de validez concordante con la dirección teóricamente prevista entre ambos constructos, sugiriendo que la autoestima disminuye cuanto mayor es el grado de FoMO.…”
Section: Discussionunclassified
“…On the grounds of the distinctions above described, comparing psychological variables acquires importance, resulting in several cross-cultural studies analyzing such constructs in undergraduates from different countries. Their findings offered major information on the similarities and differences in the students’ profiles and on the internal structures of the tests used in each country (Freiberg-Hoffmann et al, 2022; Martínez-Fernández & Vermunt, 2013; Pastor Seller et al, 2019).…”
Section: Present Studymentioning
confidence: 99%